2000
DOI: 10.2307/3871222
|View full text |Cite
|
Sign up to set email alerts
|

cDNA-AFLP Reveals a Striking Overlap in Race-Specific Resistance and Wound Response Gene Expression Profiles

Abstract: The tomato Cf-9 gene confers resistance to races of the fungal pathogen Cladosporium fulvum expressing the Avr9 gene. cDNA amplified fragment length polymorphism analysis was used to display transcripts whose expression is rapidly altered during the Avr9- and Cf-9-mediated defense response in tobacco cell cultures. Diphenyleneiodonium was used to abolish the production of active oxygen species during gene induction. Of 30,000 fragments inspected, 290 showed altered abundance, of which 263 were induced independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
129
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(143 citation statements)
references
References 55 publications
11
129
1
2
Order By: Relevance
“…This result is consistent with the transcriptional activation of a large set of ACRE genes in Cf-9-tobacco cell culture challenged with CHX for 30 min (Durrant et al, 2000) and suggests that FLARE and ACRE genes are negatively regulated by rapidly turned over repressor proteins. It also confirms the key role played by protein turnover in the initiation of the plant defense response and suggests that relief of negative regulation is important to activate plant defense.…”
Section: Effects Of a Cycloheximide Treatment On Flare Gene Expressiosupporting
confidence: 75%
See 3 more Smart Citations
“…This result is consistent with the transcriptional activation of a large set of ACRE genes in Cf-9-tobacco cell culture challenged with CHX for 30 min (Durrant et al, 2000) and suggests that FLARE and ACRE genes are negatively regulated by rapidly turned over repressor proteins. It also confirms the key role played by protein turnover in the initiation of the plant defense response and suggests that relief of negative regulation is important to activate plant defense.…”
Section: Effects Of a Cycloheximide Treatment On Flare Gene Expressiosupporting
confidence: 75%
“…Both FLARE genes and ACRE (Durrant et al, 2000) genes comprise approximately 1% of expressed genes after 30-min treatment with flg22 in Arabidopsis and Avr9 in tobacco cell cultures. Moreover, in both systems we observed that more transcripts are induced than repressed (data not shown).…”
Section: Comparison Of Acre and Flare Gene Complementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the intermediate resistance response displayed by miel1/myb30 plants, as compared with myb30 and miel1 plants, suggest the existence of additional defence-related MIEL1 targets that are functionally redundant with MYB30 during the regulation of Arabidopsis defence to pathogens. Although modulation of the expression of several RING genes in plants after treatment with different elicitors has been described [22][23][24][25] , only a few RING proteins have been involved in the regulation of plant immunity and, in most cases, their targets remain unknown. Moreover, the regulation by ubiquitination of the transcriptional activation related to disease resistance is yet poorly documented in plants.…”
Section: Discussionmentioning
confidence: 99%